Imaging comparative analysis of familial and sporadic gout in Chinese men by multijoint ultrasonography - Wen, Wen; Ma, Liwen; Dang, Wantai; Lei, Ping; Hu, Jing; Liu, Jian (Frontiers in Medicine, 2024)
Objective This study aimed to compare the imaging features of bilateral knees, ankles, and the first metatarsophalangeal joint using high-frequency ultrasonography in male patients with familial and sporadic primary gout and sought to elucidate the relationship between the presence of tophi and various clinical indicators. Method Male patients with primary gouty arthritis (GA) in the acute phase presenting to the Department of Rheumatology and Immunology at the First Affiliated Hospital of Chengdu Medical College from November 2020 to June 2022 were enrolled and classified into familial and sporadic gout groups. Comparative analyses of their clinical data and ultrasonographic imaging findings of the knees, ankles, and first metatarsophalangeal joints were performed between the groups. Univariate and multivariate logistic regression analyses, as well as receiver operating characteristic (ROC) analysis, were conducted to determine the effectiveness of significant factors in the prediction of tophi. Result In comparison to male patients with sporadic gout, those with familial primary gout exhibited lower age, body mass index, disease duration, and serum uric acid (SUA) levels. However, they demonstrated higher incidences of tophi and bone erosion (54.6% in familial gout vs. 35.1% in sporadic gout, p < 0.05; 71.2% in familial gout vs. 48.1% in sporadic gout, p < 0.05, respectively), with a greater prevalence of tophi in the right first metatarsophalangeal joint (44.2% in familial gout vs. 32.3% in sporadic gout, p < 0.05). Independent risk factors for tophi included family history (OR = 6.712), age (OR = 1.049), disease duration (OR = 1.134), and SUA levels (OR = 1.006). ROC analysis yielded an area under the curve of 0.883 (p < 0.05) for predicting joint tophi using these factors. Conclusion Male patients with familial primary GA in the acute phase experienced earlier onset, shorter disease duration compared to those with sporadic gout. They also had more affected joints, more frequent and a wider distribution of tophi, especially in the right first metatarsophalangeal joint. Family history, age, disease duration, and SUA levels are predictive of tophi formation.